All Days 2009
DOI: 10.2118/119997-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Stimulation Approach for Horizontal Power Injectors in Sandstone Reservoir, Saudi Arabia: Field Experience

Abstract: Acid stimulation systems to remove formation damage are very well established for vertical injectors, drilled during the early development of a sandstone reservoir in central Saudi Arabia. With the advent of horizontal technology, new injectors are drilled with thousands of feet of horizontal section to expose large reservoir area for injection. The conventional acid stimulation programs, applied on vertical wells, would be impractical and very expensive for horizontal wells due to the expected large quantitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Carlberg and Matthews (1973), Atkinson et al (1991), Kumar et al (2007) showed that the solubility of calcium sulfate increases by increasing the concentration of NaCl in solution and decreases by increasing the concentration of CaCl 2 . Injecting low-salinity water or chemically tuned water with high sulfate content into a formation with high calcium content will increase the calcium sulfate precipitation (Vetter and Phillips 1970;Carlberg and Matthews 1973).…”
Section: Comparison Of Chelating Agent With Low-and High-salinitymentioning
confidence: 99%
“…Carlberg and Matthews (1973), Atkinson et al (1991), Kumar et al (2007) showed that the solubility of calcium sulfate increases by increasing the concentration of NaCl in solution and decreases by increasing the concentration of CaCl 2 . Injecting low-salinity water or chemically tuned water with high sulfate content into a formation with high calcium content will increase the calcium sulfate precipitation (Vetter and Phillips 1970;Carlberg and Matthews 1973).…”
Section: Comparison Of Chelating Agent With Low-and High-salinitymentioning
confidence: 99%
“…1,2 Well-A was drilled and completed as a tri-lateral open hole oil producer. 4,5 Integrated Job Program An integrated program was considered for the first time and executed successfully in the subject tri-lateral horizontal well. 1 shows trajectories of laterals.…”
Section: Introductionmentioning
confidence: 99%
“…shows the composition of three different reservoir rocks from sandstone reservoirs that contain different iron minerals(Al Zain et al 2009 and …”
mentioning
confidence: 99%